Assessment of dental development in children with hypodontia and hyperdontia: a case control study - Dewi Ardini, Yunita; Abu Bakar, Noraini; Kamalul’lail, Nabila Farhana; Mohd Rasdi, Noor Syazwani (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
The aim is to investigate the dental development (DD) in children with hypodontia and hyperdontia compared to age, gender, and race matched controls.A match-pair case control study was conducted among children aged 5 to 14-year-old, attending the Dental Polyclinic, IIUM, from December 2011 until September 2014. Willem’s method was used to analyze the dental age (DA) using panoramic radiograph. The difference between dental age of hypodontia/hyperdontia children and the controlswas analyzed using analysis of covariance (ANCOVA). The differences between dental and chronological ages (CA) and the differences in DA and CA with the numbers of missing teeth were analyzed using t-test. Intra-class correlation coefficient between examiners ranged from 0.98-0.99. The result is that27 hypodontia and 12 hyperdontia samples were recruited and compared to a total of 78 matched controls. Both male (n=12) and female (n=15) hypodontia children had statistically significant delay in DD (p=0.000). There was no significant difference in the DD of male (n=7, p=0.811) and female (n=5, p=0.235) in hyperdontia children compared to the matched controls. No differences were observed between DA and CA with the number of missing teeth. Unlike hyperdontia children, hypodontia children showed delayed DD in comparison to age, gender, and race matched controls. There was no association between magnitudes of dental development delay in hypodontia children with the number of missing teeth. This study provides valuable baseline information for provision of better treatment planning for those hypodontia and hyperdontia children that may involve inter-disciplinary management.